2020
DOI: 10.3390/children7120299
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of a School-Based High-Intensity Interval Training Program for Older Adolescents: The Burn 2 Learn Cluster Randomised Controlled Trial

Abstract: Process evaluations can help to optimise the implementation of school-based physical activity interventions. The purpose of this paper is to describe the process evaluation of a school-based high-intensity interval training (HIIT) program for older adolescent students, known as Burn 2 Learn (B2L). B2L was evaluated via a cluster randomised controlled trial in 20 secondary schools (10 intervention, 10 control) in New South Wales, Australia. Teachers (n = 22 (55% female)) from the 10 intervention schools, delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 63 publications
(113 reference statements)
4
39
0
Order By: Relevance
“…Similarly, teachers delivering a program for senior students were provided with initial (professional learning) and ongoing (observation and feedback) support [79]. Findings from these evaluations indicated that external support likely contributed to improvements in teachers' implementation of the policy [78,80,81].…”
Section: Active Mean (%) C 78mentioning
confidence: 99%
“…Similarly, teachers delivering a program for senior students were provided with initial (professional learning) and ongoing (observation and feedback) support [79]. Findings from these evaluations indicated that external support likely contributed to improvements in teachers' implementation of the policy [78,80,81].…”
Section: Active Mean (%) C 78mentioning
confidence: 99%
“…The "Burn 2 Learn" cluster randomised trial, which delivered HIIT activity breaks twice a week for six months during curriculum time in 10 intervention schools (compared to 10 control), showed a significant improvement in older adolescents' (mean age = 16) CRF at six, but not 12 months. In contrast to previous studies, however, it observed no significant improvements in cognitive and mental health outcomes [37,51]. More pragmatic and large-scale trials, including those involving younger adolescents, are needed to assess the effectiveness and scalability of HIIT.…”
Section: Introductionmentioning
confidence: 67%
“…Schools that struggled with delivering all intervention elements were allowed to omit the third infusion occasionally [53], in order to keep schools, teachers and pupils engaged. Such modifications are not desirable, but suggest that flexibility in intervention delivery may be required [51]. Lack of time was the major barrier [53], not only for implementation of the intervention, but also for conducting secondary outcome assessments.…”
Section: Practical Challenges Of School-based Pa Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only three detailed qualitative evaluations of real-world HIIT programmes exist, but these involved adult participants as part of a workplace intervention (Kinnafick et al, 2018 ; Metcalfe et al, 2020 ; Burn et al, 2021 ). Five school-based HIIT studies included aspects of process evaluation within their outcome trials (Buchan et al, 2013 ; Leahy et al, 2019 ; Kennedy et al, 2020 ; Lubans et al, 2020 ; Costigan et al, 2015b ). However, these evaluations were either conducted quantitatively, predominantly focusing on those delivering the intervention (i.e., the schoolteachers) as opposed to those receiving the intervention (i.e., the school pupils) (Costigan et al, 2015b ; Leahy et al, 2019 ; Kennedy et al, 2020 ; Lubans et al, 2020 ), or provided inadequate detail about the qualitative methods and analysis techniques utilised (Buchan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%